The Implementation of the Electronic Information and Transactions Law in Handling Digital Disputes in Indonesia - Beni Tuce; Rita Adoe (Universitas Sains dan Teknologi Komputer, 2025)
The rapid development of digital technology has driven an increase in public activities and interactions in cyberspace, which in turn has given rise to various forms of digital disputes with increasingly complex characteristics. The Electronic Information and Transactions Law (UU ITE) serves as the primary legal instrument for regulating and resolving digital legal issues in Indonesia; however, its implementation continues to face various challenges. This study aims to analyze the implementation of UU ITE in handling digital disputes by linking normative legal provisions to empirical realities in society. The study employs a mixed-methods approach with an explanatory sequential design, integrating normative juridical analysis of UU ITE provisions with empirical data collected through quantitative and qualitative methods. Quantitative data were obtained through structured questionnaires administered to 180 respondents, while qualitative data were collected through in-depth interviews with three key informants in 2025. The findings indicate that, normatively, UU ITE has provided an adequate legal foundation for handling digital disputes; however, in practice, gaps persist between legal norms and implementation, particularly in multiple interpretations of provisions, electronic evidence, and coordination among law enforcement institutions. These findings emphasize that the effectiveness of UU ITE implementation is determined not only by the substance of the regulation but also by implementative capacity and adaptation to the dynamics of digital technology. This study contributes theoretically to the development of cyber law scholarship. It offers practical contributions to policymakers and law enforcement authorities to strengthen Indonesia's digital dispute resolution system, making it more adaptive, effective, and just.